Kombucha - fermented tea rich in nutrients and its impact on health - review - Cywka, Łucja; Nowak, Alicja; Bogusz, Klaudia; Nowak, Aleksandra; Baran, Natalia; Bielak, Adriana; Szwed, Weronika; Maksymowicz, Marcela; Machowiec, Piotr (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Kombucha is a fermented beverage, usually made by fermenting sugared black or green tea with the symbiotic culture of bacteria and yeast (SCOBY). Kombucha has gained increasing popularity in recent years, mainly due to the fact that it has been associated with some health effects. The aim of the study is to review the articles available in the PubMed database in order to learn about the health benefits of Kombucha consumption. State of knowledge: Kombucha is a source of phenolic compounds, vitamins and minerals, amino acids, enzymes, proteins and other compounds which influence biological activity. Scientific research on Kombucha has shown that it exhibits antioxidant, antibacterial, anti-inflammatory, anti-cancerogenic and antidiabetic properties. It also has a good influence on the digestive system. Kombucha consumption helps to lower cholesterol level, stimulates liver detoxification processes and also supports the proper functioning of the immune system. These properties depend on the various factors such as used products, concentration of bacteria and yeast, duration of fermentation or temperature. Summary: Kombucha tea is known as a nutraceutical. It could be used as a dietary supplement. Most of the trials have been conducted on rats or mice. Kombucha has only been involved or tested in a few human trials. It is important to spread awareness among the population about this product and its impact on people’s health, conduct more research and standardise the production methods of this beverage.